Analisis Efektivitas Kebijakan Harga Pembelian Pemerintah (HPP) Beras - Nainggolan, Lukas Bonar; Soetjipto, Widyono (Jurnal Kebijakan Ekonomi, 2016)
Analysis on the effectivity of rice price-support policy needs to be done to determine whether the rice price-support policy should be continued or not. The reason is that Indonesia is still ex- periencing problems in rice production and the farmer’s welfare of farmers when government spend large budget for rice price-support policy. This study will analyze the the effectiveness of rice price-support policy by estimating the model of rice production and grain prices with Two- Stage Least Square (2SLS) method. The result is rice price-support policy affects the grain prices effectively and it means also for the farmer’s welfare, with one time lag. Rice price-support policy also affect rice production with one time lag, because of the grain prices, as the transmission, affects rice production significantly.